Quakerism, the Forerunner of Modern Corporate Social Responsibility (CSR) - GEORGE, Olusoji James; Okanlawon, Adediji; OWOYEMI, Oluwakemi (Journal of Asian Business Strategy, 2012)
It was widely reported that 4000 Quaker families ran 74 Quaker British Banks as well more than 200 companies and that business ownership came with ‘with a deep sense of responsibility and accountability to those involved.’ It was further reported that’ --The Quaker businesspeople had the concept of truly shared stake holding and corporate responsibility in their blood, and they succeeded’. It was concluded that the nineteenth century Quaker entrepreneurs ‘illuminated a different work ethic on a more human scale between master and man.’ This was simply because their corporations were ‘doing things right’ as they considered the welfare of their workers as well as the communities where their businesses were located. It can therefore be concluded that what scholars on CSR, politicians, economists and investors are clamoring for today were achieved through the Quakers businesspeople with little or no effort; they can therefore be regarded as the forerunners of modern corporate social responsibility.